PNPO‐Mediated Oxidation of DVL3 Promotes Multiple Myeloma Malignancy and Osteoclastogenesis by Activating the Wnt/β‐Catenin Pathway - Zhendong Deng; Shanliang Sun; Nian Zhou; Yumeng Peng; Long Cheng; Xichao Yu; Yuxia Yuan; Mengjie Guo; Min Xu; Yuexin Cheng; Fan Zhou; Nianguang Li; et al. (Advanced Science)
Abstract Multiple myeloma (MM) is a cancer of plasma cells caused by abnormal gene expression and interactions within the bone marrow (BM) niche. The BM environment significantly influences the progression of MM. Celastrol, a natural compound derived from traditional Chinese medicine, exhibits significant anticancer effects. This study aimed to identify specific targets of celastrol and develop more effective and less toxic treatment options for MM. Celastrol is used as a probe to determine its specific target, pyridoxine‐5′‐phosphate oxidase (PNPO). Increased levels of PNPO are associated with poor outcomes in MM patients, and PNPO promotes MM cell proliferation and induces osteoclast differentiation through exosomes. Mechanistically, PNPO oxidizes disheveled 3M282 (DVL3), leading to abnormal activation of the Wnt/β‐catenin pathway. Based on the critical sites of PNPOR95/K117, Eltrombopag is identified as a potential therapeutic candidate for MM. In addition, the experiments showed its efficacy in mouse models. Eltrombopag inhibited the growth of MM cells and reduced bone lesions by disrupting the interaction between PNPO and DVL3, as supported by preliminary clinical trials. The study highlights the importance of PNPO as a high‐risk gene in the development of MM and suggests that Eltrombopag may be a promising treatment option.